Transient ischemic attack in the twenty first century: is it still a useful construct? - Caplan, Louis R. (Frontiers in Stroke, 2024)
Some argue that the term transient ischemic attack (TIA) has become obsolete in our age of modern advanced technology. Lets look back and analyze the term, its support and detraction, and its potential continued usefulness. The best way to begin is a review of the history of the term.